ANALISIS VISUAL TAS ANYAM PANDAN DI BENGKEL FAMILY HANDYCRAFT KAMPUNG KREATIF SUKARUAS RAJAPOLAH TASIKMALAYA - rian febrian; Aini Loita; Wan Ridwan Husen (Magelaran: Jurnal Pendidikan Seni, 2021)
This research aims to determine and describe the process of making pandanus woven pandanus handicraft production of Handycraft Workshop in Sukaruas Rajapolah Tasikmalaya Creative Village, the types produced, and analyzing the form of pandanus woven bag handicraft. This type of research is a qualitative descriptive study. The data obtained is by observation, interview, and documentation techniques. The main instrument in this study was the researcher himself used aids in the form of interviews, field notes, and a recording device in the form of a cellphone. To test the validity of the data obtained, the validity of the data technique is used in the form of an extension of participation, perseverance of observation, and triangulation. Data analysis techniques by data reduction, data presentation, and drawing conclusions.The results showed that: (1) The process of making pandanus woven bags in the Family Handycraft Workshop is divided into two techniques, namely: the process of making with a sewing machine and the process of making by hand manually. The manufacturing process includes: preparation of staples, namely making woven pandanus mats done outside the company, the process of determining the design and idea of ??a bag, then the process of assembling or producing a bag using a manual sewing machine and hand. (2) Types of bags produced include: Hand Bag covers, ribbon bags, material combination bags, simple bags and braid bags, Clutch, Sling Bags, Tote Bags and Shopping Bags. (3) The results of the analysis prove that the types of bags in the Handycraft Family Workshop are very diverse in shapes, colors, and motifs, the forms produced include trapezoid, rectangular, square, and round, colors produced from natural dyes including natural colors (without Colorant) red, purple, black, white, yellowish, brown and green pistil. The types of decorations that are applied are very diverse, namely the geometric variations such as triangles, twists, swastikas or banji, and circles or kawung motifs. Non-geometric motifs include flora and fauna motifs, and a combination of both.